Altered Gray Matter Volume, Functional Connectivity, and Degree Centrality in Early-Onset Type 2 Diabetes Mellitus - Feng, Yue; Li, Yifan; Tan, Xin; Liang, Yi; Ma, Xiaomeng; Chen, Yuna; Lv, Wenjiao; Wu, Jinjian; Kang, Shangyu; Li, Mingrui; Qiu, Shijun (Frontiers in Neurology, 2021)
Background: Early-onset T2DM patients (EOD) refer to patients diagnosed younger than 40 years. Brain structure and functional alteration underlying cognitive decline have been found in elderly population diagnosed as type 2 diabetes mellitus(T2DM), brain alterations in early-onset T2DM patients remain unclear. The abnormalities of brain volume and function connectivity patterns of early-onset T2DM will be explored in detail in our study. Methods: We enrolled 20 patients with early-onset T2DM and 20 healthy controls. Changes in brain volume were assessed using VBM and changes in resting-state function were assessed using measurement of degree centrality (DC) and function connectivity(FC). Results: Relative to healthy controls (HCs), evident gray matter loss was detected in right superior frontal gyrus (SFG) in early-onset T2DM patients , and negative association was found between urine albumin-to-creatinine ratio (UACR) and the reduction of gray matter volume. Additionally, increased DC values were detected in left superior temporal gyrus (STG), left insular, left hippocampus, which were found negatively associated with memory function. In next FC analysis based on these brain regions, elevated connectivity were shown in right posterior central gyrus (PCG), right supplementary motor area (SMA), bilateral insular, bilateral superior temporal gyrus (STG), bilateral medial and paracingulate gyrus, and these brain regions were related to part of cognitive tests. Conclusion: Decreased local gray matter volume， increased DC and FC may serve as early imaging markers for cognitive dysfunction in the population diagnosed as early-onset T2DM.